Penerapan Effective Coughing pada Tn.T dengan Penyakit TB Paru dengan Masalah Keperawatan Bersihan Jalan Napas Tidak Efektif di Ruang Nurul Jannah 301 RSI.Malahayati - Dimas Agil Latunda; Afiatika Ahsani (STIKES Columbia Asia Medan, 2024)
Pulmonary Tuberculosis is a disease caused by the bacteria Mycobacterium Tuberculosis which enters the respiratory tract and attacks the lungs so that in the alveoli there are nodules or inflammation in the walls of the alveoli which will shrink. One way to reduce secretions in pulmonary tuberculosis patients is through effective coughing exercises. This article uses a case study design and the subjects used in this case are pulmonary tuberculosis patients treated at RSI Malahayati Medan with the problem of ineffective airway clearance. The results of implementing the intervention showed that after applying the effective cough technique for 3 days the patient showed that the patient was able to expel secretions, the respiratory frequency decreased to 22 times per minute, but there were still crackles in the breath. Conclusion: applying effective coughing techniques to patients can be used to expel secretions and can reduce respiratory frequency in pulmonary tuberculosis patients. Suggestions are expected for patients to be able to take independent action (cough effectively) when experiencing problems with ineffective airway clearance.